The Controversy Surrounding the Prophet's Affliction with Magic: An Analytical Exploration of Historical and Contemporary Perspectives Among Islamic Scholars - Habiburrahaman Rizapoor; Mohammad Tayeb Athar (CV. AFDIFAL MAJU BERKAH, 2023)
This article delves into the contentious issue of whether the Prophet, peace be upon him, was afflicted by magic or not, a topic that has engendered extensive debate among Islamic scholars throughout history and into the present. The prevailing belief among the majority of Muslim scholars is that the Prophet, peace be upon him, was indeed affected by magic. They assert that this conviction is grounded in authentic and reliable narrations, leaving no room for doubt. However, they contend that the impact of magic on the Prophet did not compromise the authenticity of divine revelation. Instead, they likened it to the effects of common illnesses on human beings, solely influencing his soul and body. Conversely, a minority of contemporary scholars, who identify as rationalists and modernists, along with some classical scholars, maintain the view that the Prophet, peace be upon him, was not affected by magic. They argue that the narrations concerning this matter lack authenticity and reliability. Furthermore, they posit that accepting the notion of the Prophet's affliction with magic implies a lack of soundness and trustworthiness in the divine revelation he received during that time, attributing any perceived lapses in his senses to the alleged magical influence. For instance, some narratives indicate that the Prophet believed he had undertaken actions that he had not actually performed. This study adopts an analytical approach to investigate and analyze the subject matter. It relies on a comprehensive collection of academic articles, books, and magazine articles authored by Islamic scholars. By drawing from these reputable sources, the research aims to provide a thorough and rigorous examination of the chosen topic. The inclusion of diverse perspectives and scholarly insights contributes to a comprehensive understanding of the subject, enhancing the credibility and reliability of the study's findings. This research concludes that the prophet Mohammad was bewitched by magic but the magic was not powerful enough to have a destructive effect on his intellect. Furthermore, this magic was unable to have impact on the divine revlation that was revealed to him.